ANALISIS PANDANGAN MASYARAKAT TERHADAP PELAKSANAAN RESES DPRD PROVINSI JAWA TIMUR TAHUN 2021 DI DAPIL IX KECAMATAN NAWANGAN KABUPATEN PACITAN - jurnalmap map (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2022)
This study aims to analyze the public's response to the implementation of the East Java Provincial DPRD recess in 2021 in Dapil IX, Nawangan District, Pacitan Regency. To achieve this goal, a quantitative descriptive analysis technique of public responses was used, consisting of perceptions, attitudes and participation. The results of the descriptive analysis show that the majority have the same perception and of the five indicators the highest is the perception of the benefits of the recess program. Having a good attitude and of the five indicators the highest is the attitude of assessing the implementation of the recess program. The majority of the community participated in the implementation of the recess and of the four indicators, the highest was participation in deliberations in the kelurahan before the Recess Program was implemented.